Analysis of User Acceptance of the McDonald’s Application using the UTAUT Model - Laurencia Christine Tarika; Evi Maria (SCOPUS ID: 57093633500) (SISTEMASI, 2026)
The rapid advancement of information technology has driven increased adoption of digital applications in the fast-food industry, including the McDonald’s application, which is designed to support ordering and promotional information. However, in practice, some users still experience difficulties in using the application, highlighting the need to analyze the factors influencing its acceptance. This study aims to examine user acceptance of the McDonald’s application using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The research adopts a quantitative approach employing Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. Data were collected through an online questionnaire from 85 users of the McDonald’s application. The results indicate that performance expectancy and facilitating conditions have a significant effect on behavioral intention, while effort expectancy and social influence do not show a significant impact. Furthermore, the analysis reveals that the model demonstrates strong predictive power in explaining users’ intention to use the application. These findings suggest that perceived usefulness and the availability of technical support and facilitating resources are the key factors in enhancing user acceptance of the McDonald’s application.